The Role of Administrative Development Directorates in the National Project for Administrative Reform A Case study: "Directorates of Administrative Development at the Ministry of Water Resources and Several Subordinate Bodies" (Damascus University Journal for the economic and Political sciences, 2022)
The research addresses the reality of administrative development directorates being a critical tool in implementing the National Project for Administrative Reform in Syria and their role after being officially merged with other organizational units.The importance of this research arises from addressing the administrative development directorates given broad powers which have become a reality in all ministries. This has entailed conducting a scientific study of their recent reality evaluating this experiment along with highlighting both its advantages and disadvantages.  The research adopts deductive methodology for implementing the design of the case study including interviews, observations and documents. It aims to study the reality of working in the directorates in the Ministry of Water Resources along with a few of its bodies to find out about the possibility of activating them to play their intended part in the process of administrative development.  What is most importantly concluded from the research is that the workload required from a directorate after being merged has become really heavy, especially concerning the plenty of procedures which in turn limit the ability of the manager to concentrate on achieving administrative development. This heavy workload entails certain qualities for a manager to have such a leadership personality to motivate his/her employees. Moreover, it is important to empower divisional presidents and division chiefs to fulfill their duties and improve their skills, in addition to making employees working in administrative development directorates fully acquainted with the goals and plans on the levels of their directorates and the Ministry of Administrative Development to involve them in achieving administrative development.Search terms:-The National Project for Administrative Reform.-Administrative reform.-Administrative development
Keywords: The Role of Administrative Development Directorates in the National Project for Administrative Reform A Case study: